Mindfulness and Suicide Risk in Undergraduates: Exploring the Mediating Effect of Alexithymia - Fang, Yuan; Zeng, Baoer; Chen, Peiyi; Mai, Yiling; Teng, Shan; Zhang, Minting; Zhao, Jingbo; Yang, Xueling; Zhao, Jiubo (Frontiers in Psychology, 2019)
The present study was designed to examine the relationship between dispositional mindfulness and suicide risk in undergraduates, and it further explored the potential mediating role of alexithymia in this relationship. A total of 2,633 undergraduates completed the Mindful Attention Awareness Scale (MAAS), the Suicidal Behaviors Questionnaire—Revised (SBQ-R), and the 20-item Toronto Alexithymia Scale (TAS-20). The results indicate that mindfulness and suicide risk were negatively correlated, and alexithymia partially mediated the relationship between mindfulness and suicide risk only in the female undergraduates. Moreover, only the difficulty in identifying feelings (DIF) factor of alexithymia mediated the relationship between mindfulness and suicide risk in the female undergraduates. These findings contribute to the potential mechanism that explains the relationship between mindfulness and suicide risk. Furthermore, it is possible to implement mindfulness in the suicide intervention of alexithymic individuals.